DrIVE-MATH Project: Case Study from the Polytechnic of Porto, PT - Pinto Carla M.A; Mendonça Jorge; Nicola Susana (De Gruyter, 2022)
The School of Engineering of the Polytechnic of Porto (ISEP) has embraced the DrIVE-MATH project, since September 2017. Active-learning (AL) techniques were implemented in several Math courses, namely Linear Algebra and Analytic Geometry, Probability and Statistics, Statistical Models, Computational Mathematics, and Differential and Integral Calculus I. In this paper, we will share the strengths, weaknesses, opportunities and threats of the implementation of the active-learning (AL) environment in these courses. We will detail the courses' plans, emphasizing the syllabus, pedagogical methodologies, assessment methods, students' perceptions, and other related issues. Several questionnaires were posed to the students enrolled in these Math courses during the last three academic years. The statistical analysis of the gathered data provided valuable indications of students' perceptions on the effectiveness of several AL methods, on the development of their own essential (soft+hard) skills. These skills will be a valuable resource to their future professional and personal lives. The 5th Industrial Revolution is just around the corner.